Evaluating of In-service Training Activities for Teachers in Turkey: A Critical Analysis - Yolcu, Hüseyin; Kartal, Sadık (Horizon Research Publishing Co., Ltd., 2017)
The aim of this study is to examine the in-service training activities organized by the Ministry of Education of Turkey for the last 15 years (between 2001 and 2015). Two main starting points were identified in commentaries on in-service training; (1) Teacher needs which are part of the field of teacher training (2) Technological developments related to education, especially digital education, which have taken place in recent years in educational settings. In the study, it has been found that approximately a thousand centralized training activities have been offered every year in the analyzed periods. Activities have also been organized in the areas of professional development and general culture as well as field-specific activities. It has also been found that the training activities are addressed to teachers at all types and levels of schools attached to the Ministry of National Education (MoNE). The effectiveness of in-service training activities organized by MoNE should be evaluated.
Keywords: 4. Education